PENDEKATAN KUALITATIF DALAM PENELITIAN PENDIDIKAN (Konsep, Implementasi, dan Tantangan) - Faiz Muhtadi; Desy Eka Citra Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the definition and characteristics of a qualitative approach in educational research, the basic concepts of qualitative research, its implementation in educational research, the challenges in qualitative educational research, and the contributions and benefits of a qualitative approach. This research is a library research, by searching for and analyzing relevant literature. The method used to collect data is documentation, through archives and books related to theories, arguments, laws, and research issues. From this study, the following results were obtained: First , qualitative research aims to understand the subject's experience through behavior, perception, and action. This is done by describing it using words. In addition, this study also describes and analyzes natural social phenomena and activities. Second, qualitative research uses an inquiry approach to understand certain ideas, symbols, and phenomena. This research has characteristics such as focusing on details, using various methods, and being natural and comprehensive. The quality of the research is presented in narrative form. Third, the application of a qualitative approach in educational research includes the methods used by researchers to collect and explain data. The implementation in educational research includes research planning, data collection techniques, data analysis, and validity and validity. Fourth, Some of the main challenges in qualitative research are researcher subjectivity and interpretative bias, difficulty maintaining data validity and credibility, long-term data collection, complexity of data analysis, limited field access, and difficulty generalizing research results. Fifth, Qualitative research is based on post-positivism, because this method is effective for studying natural objects, which is the opposite of experiments. The purpose of qualitative research can be seen from the description of the research object, revealing the meaning behind the phenomenon, and explaining the phenomena that occur.